1998
DOI: 10.1097/00007890-199804150-00017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Evaluation of Glycerolized Cadaveric Donor Skin

Abstract: In conclusion, preservation of skin in 85% glycerol reduces the risk of bacterial transfer to the recipient and allows an increase in yield of cadaver skin of approximately 10%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 19 publications
0
24
0
7
Order By: Relevance
“…All cells are nonviable but the collagen and elastin fibers are well preserved using this method (Richters et al 1996). In addition, glycerol 85% is a slow but effective in-activator of microorganisms (van Baare et al 1994(van Baare et al , 1998a.…”
Section: Introductionmentioning
confidence: 99%
“…All cells are nonviable but the collagen and elastin fibers are well preserved using this method (Richters et al 1996). In addition, glycerol 85% is a slow but effective in-activator of microorganisms (van Baare et al 1994(van Baare et al , 1998a.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that fresh skin in general has an antimicrobial effect against E. coli, S. aureus, but it does not necessary means CPA and GPA also have an antimicrobial effect. According to one study, 85% GPA has a strong antimicrobial effect [21]. But the results of this study showed CPA has a mild antimicrobial effect against 6 types of bacterial species.…”
Section: Discussionmentioning
confidence: 60%
“…We set out to develop a dermal substitute from glycerol preserved allografts more than a decade ago, which was intended to have the following key advantages: native collagen and elastin matrix, easy storage and handling, inactivation of virus and micro-organisms [45,46] and most importantly, a non-profit product that could be available to a larger number of patients. The extreme high cost of dermal substitutes today impedes their widespread application and benefit for those who need it the most.…”
Section: Discussionmentioning
confidence: 99%